Rationalizing the Choice of Housing on Cultivable Land: Is Cash-Return the Only Determinant? - Ahmed, Zobayer (Journal of Social and Development Sciences, 2013)
Society faces numerous problems due to high population growth where housing along with other settlements is a notable concern. Horizontal expansion of housing on cultivable land in rural area reduces the availability of land for cultivation. The study is a combination of both quantitative and qualitative in nature based on primary data, carried out in a village in Comilla, an eastern district of Bangladesh during April 2012. The study finds that the households receive returns both in cash as well as in kind from new homesteads made on cultivable land. The cash benefit received by households at new place is Tk. 156238.14 on an average per year in 2011 price and on an average the cash investment per year in 2011 price (inflation adjusted) for housing is Tk. 213108.1818 (weighted average). This clearly indicates a cash loss from housing on cultivable land from household’s perspective. However, statistically the cash investment for housing in rural area is not significantly different from the cash return received by the households at 5% level of significance. Thus it becomes an important question whether the household’s choice of making new home on cultivable land is a rational choice or not. Further, the amount of money each household spent for housing could have been used for a higher cash return through some alternative investments. The study reveals, households derive positive utility (non cash returns) from new homes notwithstanding cash loss and other investment options forgone. The study further argues that if the government or any authority is to take some steps regarding the declining trend of cultivable land in rural areas, the perspectives of the households must be considered with great attention.